2'-O-Methyl at 20-mer Guide Strand 3' Termini May Negatively Affect Target Silencing Activity of Fully Chemically Modified siRNA - Sarah M. Davis; Jacquelyn Sousa; Lorenc Vangjeli; Matthew R. Hassler; Dimas Echeverria; Emily Knox; Anton A. Turanov; Julia F. Alterman; Anastasia Khvorova (Elsevier, 2020)
Small interfering RNAs (siRNAs) have the potential to treat a broad range of diseases. siRNAs need to be extensively chemically modified to improve their bioavailability, safety, and stability in vivo. However, chemical modifications variably impact target silencing for different siRNA sequences, making the activity of chemically modified siRNA difficult to predict. Here, we systematically evaluated the impact of 3' terminal modifications (2'-O-methyl versus 2'-fluoro) on guide strands of different length and showed that 3' terminal 2'-O-methyl modification negatively impacts activity for >60% of siRNA sequences tested but only in the context of 20- and not 19- or 21-nt-long guide strands. These results indicate that sequence, modification pattern, and structure may cooperatively affect target silencing. Interestingly, the introduction of an extra 2'-fluoro modification in the seed region at guide strand position 5, but not 7, may partially compensate for the negative impact of 3' terminal 2'-O-methyl modification. Molecular modeling analysis suggests that 2'-O-methyl modification may impair guide strand interactions within the PAZ domain of argonaute-2, which may affect target recognition and cleavage, specifically when guide strands are 20-nt long. Our findings emphasize the complex nature of modified RNA-protein interactions and contribute to design principles for chemically modified siRNAs.